Avaliação fisiológica da aroeira (Schinus terebinthifolius Raddi) sob déficit hídrico com vista para o reflorestamento - SILVA, Maria Alice Vasconcelos da (2007)
This work aimed to study the effect of water deficit on gas exchange, leaf water potential, dry matter production, and some biochemical aspects of Schinus terebinthifolius Raddi. young plants. A research project was developed, under greenhouse conditions, at the Laboratório de Fisiologia Vegetal, Departamento of Biologia of Universidade Rural de Pernambuco between November, 2005 to February, 2006. Seedlings with 3 month-old and sexually propagated were cultivated in containers containing 5.5 kg of soil. The entirely randomized experimental design was used, with four water treatments (100%, 75%, 50% and 25% to field capacity-FC), with four replicates. Plants under 25% FC were re-watered to 100% FC once after stomatal closure. After 15 days of acclimation period have started the water treatments. The experimental period lasted for 74 days. Transpiration (E), diffusive resistance (Rs), leaf temperature (Tfol), air temperature (Tar), relative humidity of the air (UR), photosynthetically active radiation (PAR), and vapor pressure deficit (VPD) were evaluated at midday each seven days. At the end of the experimental period, leaf water potential (Yf) was measured at midday. Leaves (LDM), stems (SDM), roots (RDM), and total dry masses (TDM), root to shoot ratio (R/Sh), and leaves (LBA), stems (SBA) and roots biomass allocation (RBA) were determined. In addition, carbohydrates, free proline, soluble protein and free amino acids contents were analyzed. In plants under 25% field capacity, stomatal closure was observed after 11 days of water treatments. At the time plants were re-watered to 100% FC. After 24 h plants re-watered recovered the stomatal aperture, which remained open until the end of the experimental period. Water deficit decreased the leaf water potential (Yf) in plants grown at 25% FC (-2.2 MPa) when compared with the 100% FC treatment (-1.1 MPa). Plants grown under 75% FC producted higher LDM, SDM and RDM than the other treatments. Differences among treatments to biomass allocation were not observed, but there was a tendency to plants grown under 25% of FC to increase more biomass allocation than the other treatments. The water stress reduced carbohydrates contents and increased soluble protein and amino acids. However, differences to proline content were not verified among water treatments. These results suggest that this species is tolerate to low humidity levels in the soil and that the level of 75% of FC is the best to cultivate it in the initial fase of development.